DAYA TAHAN TUBUH PEMAIN FUTSAL ACADEMY LEBAH LAMPUNG DENGAN LATIHAN SLOW INTERVAL - Bimo Mauladi; Dimas Duta Putra Utama; Dwi Priyono; Ardiyan Cahyadi; Heru Sulistianta (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The purpose of this study was to determine the effect of slow interval training on the experimental group and the influence of the control group on increasing the immune system of Lampung bee academy players. The study using the True Experimental method was used with a sample of twenty players from the Lampung Bee academy. For the data collection method using a 15-minute run test or a balke test. Data analysis techniques that use t-tests. The results showed; 1) There is an influence on increasing the endurance of the experimental group of futsal academy players using slow interval training, which is evident from the calculated t values (11.75) and t table (2.903). (2) There was no effect of increasing the endurance of the futsal academy player control group, as evidenced by the calculated t values (1.438) and t table (2.093).